PENDIDIKAN KARAKTER BERBASIS PESANTREN DI PONDOK PESANTREN AL ASHRIYAAH NURUL IMAN PARUNG BOGOR - Siskandar Siskandar; Susanto Susanto; Ahmad Muhammad Syafi’i (el-Moona: Jurnal Ilmu Pendidikan Islam, 2019)
Islamic boarding schools are part of national education that existed before the independence of the Republic of Indonesia, and even allegedly as an educational institution that is a typical Indonesian educational institution. In addition to developing a formal education system, one of the characteristics of the pesantren education system is the character building of students or santri through a series of activities carried out. Al Ashriyyah Islamic Boarding School Nurul Iman Parung Bogor is one of the boarding schools that develops a formal education system and equips students or students with a variety of activities to shape character. Character education aims to create students or students who have the knowledge and character inherent in students. This study aims to illustrate how character education in pesantren is carried out. This article uses descriptive qualitative research methods. Based on the research, it was found out that the character education in Pesantren Al Ashriyaah Nurul Iman was carried out through additional activities outside of compulsory study hours in the form of arts, sports and students' entrepreneurship.